PENGENDALIAN KAS PADA PT. KUKAR MANDIRI SHIPYARD - -, Varianto - (EKONOMIA, 2014)
In this reformation era, budgeting is essential for surveillance work (controlling). Budget has two important roles within the company. On the one hand, the budget serves as a tool for planning, budgets and on the other hand acts as a short-term controllers for an organization. This study was conducted at PT. Kukar Mandiri Shipyard which is a company engaged in the services of shipbuilding and ship repair. Cash on this company sometimes still exaggerated and sometimes shortcomings, this is because the predictions of payment from the owner of the vessel often miss the due and sometimes uncertain sales outlook so if it misses, the prediction of sales purchase will also slip and receipt of working capital, which has not made sure that the budget is not yet effective.The problem in this research is "Are Controlling cash at. PT. Kukar Mandiri Shipyard done effectively? ". The purpose of this reseach is to determine whether or not the effective controlling cash in PT. Kukar Mandiri Shipyard. The analysis tool used is the analysis of variance is comparing the budget with the realization and use the ratio to determine the effectiveness of irregularities.From the analysis and discussion, it can be concluded as follows: On the first to fourth quarter of 2012 revenue in cash from operations, experiencing irregularities between realization and budget by 88.37%, but still within the category are quite effective as it ranges between 80-90%. On the receipt of cash from working capital and investment activity on the first to fourth quarter of 2012 deviations between actual experience with a budget of 87.47% but still quite effective because the category is still around between 80 - 90%.Overall acceptance of the results is still around 80-90%, so it is still included on the quite effective category. Categories of operational definitions effective if > 80%. So in conclusion, the cash budget in PT. Kukar Mandiri Shipyard has been effective. According to the hypothesis that reads "Cash Control has not been effective in PT. Kukar Mandiri Shipyard " was rejected.